Caught between Scylla and Charybdis? Regulating bank leverage when there is rent seeking and risk shifting - Viral V. Acharya; Hamid Mehran; Anjan Thakor (Federal Reserve Bank of New York, 2010)
Banks face two different kinds of moral hazard problems: asset substitution by shareholders (e.g., making risky, negative net present value loans) and managerial rent seeking (e.g., investing in inefficient 'pet' projects and consuming perquisites that yield private benefits). The privately optimal level of bank leverage is neither too low nor too high: It balances efficiently the market discipline imposed by owners of risky debt on managerial rent seeking against the asset substitution induced at high levels of leverage. However, when correlated bank failures can impose significant social costs, governments may have no option but to bail out bank creditors. Anticipation of this generates an equilibrium featuring systemic risk in which all banks choose inefficiently high leverage to fund correlated assets and market discipline is compromised. A minimum equity capital requirement can rule out asset substitution but also compromise market discipline by making bank debt too safe. The optimal capital regulation requires that a part of bank capital be unavailable to creditors upon failure, and be available to shareholders only contingent on good performance.
Keywords: G21; G28; G32; G35; G38; 330; Market discipline; asset substitution; systemic risk; bailout; forbearance; moral hazard; capital requirements; Bankgeschäft; Risiko; Moral Hazard; Management; Rent Seeking; Kapitalstruktur; Theorie